Corrosion Behavior and Microhardness of a New B4C Ceramic Doped with 3% Volume High-Entropy Alloy in an Aggressive Environment - Alberto Daniel Rico-Cano; Julia Claudia Mirza-Rosca; Burak Cagri Ocak; Gultekin Goller (Metals)
The aim of this paper is to study both the mechanical and chemical properties of a new material composed of B4C doped with 3% volume of CoCrFeNiMo HEA by the spark plasma sintering technique. Scanning electron microscopy and microhardness were used to characterize the composite microstructure and hardness. Corrosion behavior was studied by corrosion potential, corrosion rate and electrochemical impedance spectroscopy, where the equivalent circuit was obtained, characterized by the presence of the Warburg element. The addition of HEA resulted in a more compact microstructure, filling pores and inhibiting ceramic grain growth. A microhardness statistical analysis revealed that the sample followed a normal distribution, which suggests that the sample has a homogeneous structure. The doped material exhibits excellent corrosion resistance in artificial seawater, where its chemical interaction occurs in two steps, with an important diffusional component. This study highlights the potential for use in environments where both corrosion resistance and mechanical strength are critical factors.